Situational Strategic Projection in the teaching-learning of the medical professional: The experience lived with the theme of domestic violence against women - Alves, Anderson Kallyu Gomes; Rodrigues, Ane Caroline da Silva; Silva, Bruna Eduarda Veras da; Moita, Clara Patriarca; Neto, Claudio Henrique Simões; Pereira , Waltair Maria Martins (Seven Editora, 2023)
The lack of knowledge about the mandatory notification of domestic violence against women and the low importance of surveillance, of this disease, is a reality today in the exercise of the activities of the physician in the activities of Primary Health Care. The teaching-learning process of the medical professional must be focused on the competencies and skills for him to develop the activities of health care, decision-making, communication, leadership, administration and management of services, and permanent education of work teams, and the teaching-learning of situational strategic planning provides this requirement. This experience report aimed to work with situational strategic planning, programming actions for health promotion and prevention of diseases and injuries, on domestic violence against women, a topic of great relevance in the epidemiological profile of the area attached to the health unit, practice scenario of the course, performing the programmed activities in an integrated way with the multidisciplinary team of the Family Health Strategy and other social equipment. existing in a Community of a peripheral neighborhood of the municipality of Belém, state of Pará. The programmed actions were centered on health promotion and disease prevention, which were amplified due to the resources used for the discussion of the subject, such as the infographic and the short-term film, produced to work with groups of organized individuals, for information and communication actions on the subject. The learning of medical students was fully attended and the initiation of surveillance work against domestic violence against women was translated as a contribution of the Federal University of Pará to the organization of primary care activities in the Riacho Doce Family Health Strategy. DOI:https://doi.org/10.56238/devopinterscie-199